PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI ISLAMI TERHADAP KEPUASAN KERJA KARYAWAN KOPPONTREN - Inayah, Nurul; Rohmah, Siti Nur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purposes of this study are (1) to determine and analyze the existence of organizational culture (X1) has a significant effect on employee job satisfaction (Y) (2) To determine and analyze the existence of Islamic compensation (X2) has a significant effect on employee job satisfaction ( Y). (3) To find out and analyze organizational culture (X1) and Islamic compensation (X2) together have a simultaneous effect on employee job satisfaction (Y). The result of the research is that the significance level is 0.004 < 0.05. Therefore, the probability level is much smaller than 0.05 using a significance level of 5% or 0.05. It can be said that there is a jointly significant influence of organizational culture and compensation on job satisfaction of employees of Koppontren Ausath Darussalam Blokagung Tegalsari Banyuwangi. Then from the results of the coefficient of determination (R2) of 0.837 which shows that the organizational culture variable (X1) and Islamic compensation (X2) simultaneously affect the employee job satisfaction variable (Y) of 83.7% which means the organizational culture variable (X¬1) and Islamic compensation (X2) has a dominant influence on employee job satisfaction (Y).